Antigenic variants of influenza B viruses isolated in Japan during the 2017‐2018 and 2018‐2019 influenza seasons - Kato‐Miyashita, Sari; Sakai‐Tagawa, Yuko; Yamashita, Makoto; Iwatsuki‐Horimoto, Kiyoko; Ito, Mutsumi; Tokita, Akifumi; Hagiwara, Haruhisa; Izumida, Naomi; Nishino, Tamon; Wada, Noriyuki; Koga, Michiko; Adachi, Eisuke; et al. (Influenza and other respiratory viruses, 2020)
Background Here, we genetically and antigenically analyzed influenza B viruses (IBVs) isolated in Japan during the 2017‐2018 and 2018‐2019 influenza seasons. Methods A total of 68 IBVs (61 B/Yamagata/16/88‐like [B/Yamagata]‐lineage and 7 B/Victoria/2/87‐like [B/Victoria]‐lineage) were antigenically and genetically characterized by using hemagglutination inhibition (HI) assays and phylogenetic analysis, respectively. The susceptibility of IBVs to neuraminidase (NA) inhibitors was assessed by using a fluorescence‐based NA inhibition assay. Results All 61 B/Yamagata‐lineage isolates were genetically closely related to B/Phuket/3073/2013, the vaccine strain for these two seasons. Eleven B/Yamagata‐lineage isolates tested were antigenically similar to B/Phuket/3073/2013 by the HI test. Seven B/Victoria‐lineage isolates were genetically closely related to B/Texas/02/2013, the WHO‐recommended vaccine strain for the 2017‐2018 season; however, they were antigenically distinct from B/Texas/02/2013 with an eightfold or 16‐fold difference in HI titer. Of these 7 isolates, 4 possessed a two‐amino‐acid deletion at positions 162 and 163 in hemagglutinin (HA) and the other 3 had a three‐amino‐acid deletion at positions 162‐164 in HA. Importantly, the variants with the three‐amino‐acid deletion appeared to be antigenically different from the B/Colorado/06/2017 virus with the two‐amino‐acid deletion, the vaccine strain for the 2018‐2019 season with a fourfold or eightfold difference in HI titer. One B/Yamagata‐lineage isolate carrying a G407S mutation in its NA showed a marked reduction in susceptibility to zanamivir, peramivir, and laninamivir. Conclusions These results highlight the need for continued monitoring for the prevalence of the antigenic variant with the three‐amino‐acid deletion and the variant with reduced NA inhibitor susceptibility.